DETERMINAN KUALITAS LAPORAN KEUANGAN DENGAN SISTEM TEKNOLOGI INFORMASI SEBAGAI PEMODERASI (STUDI EMPIRIS PADA BADAN LAYANAN UMUM DI KEMENKES INDONESIA) - Irma; Darminto, Dwi Prastowo; Darmansyah (FEB Universitas Sam Ratulangi Manado, 2023)
The purpose of this research is to analyze the relationship between the variables of human resources competence, Internal Audit and organizational commitments as well as information technology systems as moderation in their influence on the quality of financial reporting at BLU Kemenkes Ministry hospital. The data collection technique uses non-probability sampling by distributing 136 questionnaires to financial compilers. Analysis method using Moderated Regression Analysis (MRA) with SPSS 25 application. The results of the research showed that the competence of SDM, internal audit affects the quality of financial statements, while the organization's commitment variables have no influence on financial reporting quality. Information technology systems have been shown to moderate the relationship between SDM competence and internal audit of the quality of financial statements